2017
DOI: 10.1080/14703297.2016.1273790
|View full text |Cite
|
Sign up to set email alerts
|

Retrospection and reflection: The emerging influence of an institutional professional recognition scheme on professional development and academic practice in a UK university

Abstract: Raising the quality and profile of teaching and student learning is something universities across the UK are aspiring to achieve in order to maintain reputations.Currently, the UK Professional Standards Framework (UKPSF) provides a standard by which academic staff can gain professional recognition for their academic practice and many UK universities are now offering professional development opportunities via inhouse recognition schemes, based on retrospection and reflection, to enable staff to achieve an HEA F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…The 2016 HE White Paper is also ambiguous in places: for example, it emphasises the further dominance of a business modelled 'market' approach to HE whilst, on the other hand, the proposals are paralleled by a draft of contradictory regulation of standards. It is these ambiguities in the design of the TEF that has led to concerns expressed in an emerging body of literature(Frankham 2017;Gibson 2016;Ingham 2016;Neary 2016;Robinson and Hilli 2016;Snowden and McSherry 2017;Van der Sluis et al 2017). For example, whilst generally supporting the premise that more information on the quality of teaching should be available to potential students,Ashwin (2017) suggests the crude performance mechanisms of the TEF will not be representative of the complexities interwoven into what constitutes 'good teaching'.…”
mentioning
confidence: 99%
“…The 2016 HE White Paper is also ambiguous in places: for example, it emphasises the further dominance of a business modelled 'market' approach to HE whilst, on the other hand, the proposals are paralleled by a draft of contradictory regulation of standards. It is these ambiguities in the design of the TEF that has led to concerns expressed in an emerging body of literature(Frankham 2017;Gibson 2016;Ingham 2016;Neary 2016;Robinson and Hilli 2016;Snowden and McSherry 2017;Van der Sluis et al 2017). For example, whilst generally supporting the premise that more information on the quality of teaching should be available to potential students,Ashwin (2017) suggests the crude performance mechanisms of the TEF will not be representative of the complexities interwoven into what constitutes 'good teaching'.…”
mentioning
confidence: 99%
“…Digital submissions may come in the form of essays, reports, reflections or dissertations depending on the level or discipline of study. Participants (n=58) were selected based on their engagement with the two universities teaching recognition schemes (van der Sluis, Burden, & Huet, 2017 ); hence, they were perceived as having an interest in pedagogy. Participants were selected from different disciplinary areas and ranged from lecturers to professors.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between HEA accredited CPD and the enhancement of teaching and learning is explored by Thornton (2014), van der Sluis et al (2016;, Shaw (2017) and Botham (2017a) who suggest that the relationship between the recognition schemes and the enhancement of practice needs to be considered with care. Van der Sluis et al (2017), Shaw (2017) and Thornton (2014) found that some academics reported changes to their teaching practice, but these changes were moderate in nature. Nevertheless, changes were found beyond the context of direct teaching and/or classroom practice, such as increased confidence to engage in mentoring and leadership (Botham, 2017a;van der Sluis et al, 2017).…”
Section: Understanding the Experience Of Hea Accredited Cpdmentioning
confidence: 99%
“…Van der Sluis et al (2017), Shaw (2017) and Thornton (2014) found that some academics reported changes to their teaching practice, but these changes were moderate in nature. Nevertheless, changes were found beyond the context of direct teaching and/or classroom practice, such as increased confidence to engage in mentoring and leadership (Botham, 2017a;van der Sluis et al, 2017). The latter is a particular focus of a Senior Fellowship application (Lea and Purcell, 2015).…”
Section: Understanding the Experience Of Hea Accredited Cpdmentioning
confidence: 99%